Showing—intentional communication—in dogs (Canis familiaris) - Heberlein, Marianne T. E.; Oberliessen, Lina V.; Virányi, Zsófia; Lutonsky, Christiane; Turner, Dennis C. (Frontiers in Psychology, 2025)
IntroductionThe characterization of imperative pointing as intentional communication, aimed at eliciting specific actions from a partner, has been debated, with some suggesting it reflects an understanding of others as causal agents rather than attributing intentional states to them. While gaze alternation has been identified as an important form of intentional communication in humans and apes, its interpretation in dogs remains unclear.MethodsThis research investigates dogs’ capacity for gaze alternation and other showing behaviors, examining their flexibility in adjusting to the cooperativeness or knowledge state of their human partners. Two experiments were conducted: (1) hiding food in the presence of dogs either with or without their owners observing the hiding procedure, and (2) hiding food in the presence of dogs and a cooperative or a competitive human partner. In the first experiment the behaviors of 21 dogs and in the second experiment 23 dogs were analyzed.ResultsDogs exhibited more gaze alternation and food-directed showing behaviors when their owner lacked knowledge of the food location and in the presence of a cooperative partner. Conversely, they showed an empty hiding place to the competitive partner, suggesting an understanding of the partner’s intention to consume the hidden reward.DiscussionIn the two independent experiments, we showed how flexibly dogs adapt their showing behavior to the knowledge or expected behavior of their human partners. These findings confirm dogs’ comprehension of the informative value of their behavior, suggesting that their showing behavior is a form of intentional communication.